Comorbidities present in hidradenitis suppurativa. Issue 2 (29th March 2022) - Stokes, Madison M.; Holahan, Heather M.
Abstract: Hidradenitis suppurativa (HS) is characterized by a chronic, inflammatory cascade that occurs within the apocrine glands and produces inflammatory papules and nodules, abscesses, and scarred, fistulizing sinus tracts. Despite evidence that patients with HS have a two‐fold greater comorbidity burden in comparison to both psoriasis patients and the unaffected, healthy population; the identification of risk factors and the spectrum of co‐existent medical illnesses have not been fully characterized. Recent data has elucidated increased prevalence of several cutaneous, psychologic, gastrointestinal, musculoskeletal, endocrine, conditions in patients with HS. Treatment modalities can be optimized based on shared cytokine profiles and immune dysregulation. Screening guidelines have been recommended based on prevalence, in order to provide better health outcomes for these patients.